Modeling of hydration products and strength development for high-volume fly ash binders - Krishnya, S.; Herath, C.; Elakneswaran, Y.; Gunasekara, C.; Law, D.W.; Sujeeva, S. (Elsevier, 2022)
Partial replacement of cement using fly ash, as an environmentally friendly approach, has gained increased attention in construction practice. The realistic prediction of microstructure and mechanical properties of fly ash blended cement paste is therefore noteworthy for many practical applications including selection of construction material and their appraisal of design. In this research work, an integrated framework is proposed and demonstrated for predicting the hydration products and compressive strength of high-volume fly ash binders. The prediction framework is designed to have multiple stages. For computing the hydrates of blended cement paste, a coupled hydration model with thermodynamic modelling is developed. A hierarchical model that captures the development of the paste via multiple levels (from C-S-H globules to blended cement paste) is used subsequently to predict the compressive strength as a function of hydration period. Here, unlike previous works, the formation of C–S–H is realistically modelled by distinguishing it into low- and high-density C–S–H. A series of experiments (including XRD Rietveld analysis, thermo gravimetric analysis, selective dissolution, mercury intrusion porosimetry and compression tests) are performed; hence the predictability of the developed work is assessed by comparing the predicted results with experimental data. A very good agreement is seen between the predicted results (hydration products, pore volume and compressive strength) and experimental results, indicating that the proposed model can be applicable to the high-volume fly ash cement paste to reliably capture the hydrates and compressive strength. It is further noted that with an increase in fly ash replacement ratio, the capillary porosity increases, while the reaction rate and compressive strength decrease.
Keywords: High-volume fly ash cement paste; Compressive strength; Hydration products; C-S-H; Capillary porosity; Hierarchical model